Poly-Saora robotic jellyfish: swimming underwater by twisted and coiled polymer actuators - Hamidi, Armita; Almubarak, Yara; Rupawat, Yash Mahendra; Warren, Jeremy; Tadesse, Yonas (Smart materials and structures, 2020)
Jellyfish are energy-efficient swimmers due to the muscle-powered flapping of their soft bell that facilitates a unique energy recapture mechanism. In this paper, we present a bio-inspired jellyfish robot named Poly-Saora that mimics the swimming behavior of the jellyfish species Black sea nettle (Chrysaora achlyos). An assembly-based fabrication method is used to create the Poly-Saora that is developed mainly with polymeric materials (95% of the robot by volume). Twisted and coiled polymer (TCP) actuators are successfully implemented in this robot and show great potential for underwater applications. The influence of different parameters such as the amplitude of the input power, the actuation frequency, and the lifecycle of the actuator are investigated underwater. A full characterization of 6-ply TCP muscles is demonstrated. An actuation strain of ∼10% is achieved in water at a frequency of 0.1 Hz and 50 kPa load. When integrated into the jellyfish, the TCP was able to bend a single bell by 17°. Poly-Saora was able to swim a vertical distance of 180 mm in 220 s with four TCP actuators each confined in a separate conduit. The robot mimics the swimming behavior of a real jellyfish by contracting the bell segments through the activation of the actuators, which generates forced water circulation under the bell in a pulsating rhythm, consequently creating a vertical movement of the robot. Overall, Poly-Saora presents a model of an underwater system that is driven by stimuli-responsive polymer materials and has unique advantages over conventional rigid robots due to their lightweight, muscle-like structures, silent actuation and ease of manufacturing. This robot can be used for safe interaction with other underwater species and their natural habitats when fully developed.